Rethinking Arab democratization elections without democracy - Sadiki, Larbi (Oxford : Oxford University Press, 2009)
How do Arab countries democratise? This is the key question this book seeks to answer. To this end, the book assesses Arab democratic experiments and analyzes the opportunities and perils, highlighting the peculiarities of democratic transitions in the Arab Middle East.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Democratization -- Arab countries; Democracy -- Arab countries; Elections -- Arab countries; Islam and politics -- Arab countries; Arab countries -- Politics and government